Consumer behaviour towards Ready-To-Eat (RTE) food on food-related lifestyle in Peninsular Malaysia / Ana Batrisyia Azman and Norsyakirah Mazlan - Azman, Ana Batrisyia; Mazlan, Norsyakirah (2021)
Food is essential for human growth and ensuring the normal functioning of the body parts. Consumer interest in ready-to-eat (RTE) food is growing due to changes in lifestyles among the urban residents in Malaysia. This research aims to identify the determinants of food-related lifestyle on consumer behaviours towards ready-to-eat (RTE) food and to determine the most influential food-related lifestyle determinants of consumer behaviours towards RTE food consumptions in Peninsular Malaysia. Four determinants were analysed (health-orientation, taste-orientation, convenience-orientation, and tradition-orientation) to explain the ready-to- eat food towards consumers’ food-related lifestyles. In this study, a quantitative method and the descriptive research design were applied to fulfil the research objectives and as guideline to collect and analyse the data. The close-ended structured questionnaires through online survey were applied to gather data from 385 consumers in Peninsular Malaysia via convenience sampling. This study is focusing on the six (6) most developed states (Federal Territory of Kuala Lumpur, Selangor, Malacca, Perak, Johor, and Penang) where the trend of urbanisation has brought in lifestyle changes in urban areas. The research revealed that convenienceorientation is the most influential factor of consumer behaviour towards RTE food. Thus, the findings throughout this paper can be useful for the RTE food manufacturers in planning their marketing strategies by understanding the consumer behaviours towards RTE food.